2007
DOI: 10.1007/s10865-007-9133-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between resting blood pressure and acute pain sensitivity: effects of chronic pain and alpha-2 adrenergic blockade

Abstract: This study tested for alpha-2 adrenergic mediation of the inverse relationship between resting blood pressure and acute pain sensitivity in healthy individuals. It also replicated limited prior work suggesting this inverse blood pressure/pain association is altered in chronic pain, and provided the first test of whether chronic pain-related changes in alpha-2 adrenergic function contribute to these alterations. Resting blood pressure was assessed in 32 healthy controls and 24 chronic low back pain participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…If chronic pain is conceptualized more broadly as a chronic physiological stressor, one possibility is that chronic stress-related activations of the sympathoadrenomedullary and hypothalamo-pituary-adrenocortical axes may contribute to increased incidence of metabolic syndrome (Nieuwenhuizen & Rutters, 2008; Rosmond, 2005). Other studies provide evidence for chronic pain-related reductions in baroreflex sensitivity indicating altered autonomic function (Chung et al, 2008; Furlan et al, 2005; Reyes Del Paso, Garrido, Pulgar, Martín-Vázquez, Duschek, 2010; Spaziani, 2008), absence of natural analgesia typically associated with BP elevations (Bruehl, Chung, Diedrich, Diedrich, Robertson, 2008; Olsen et al, in press; Bruehl, Chung, & Chont, 2010; Bruehl, Chung, Ward, Johnson, & McCubbin, 2002), and possible alterations in neurotransmitter function including opioid (Bruehl & Chung, 2004; Bruehl, McCubbin, & Harden, 1999; Spaziani et al, 2008) and alpha-2 adrenergic (Chung et al, 2008) systems. These findings suggest that chronic pain is associated with changes in both the central and peripheral nervous systems that could provide alternative pathways for elevated CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…If chronic pain is conceptualized more broadly as a chronic physiological stressor, one possibility is that chronic stress-related activations of the sympathoadrenomedullary and hypothalamo-pituary-adrenocortical axes may contribute to increased incidence of metabolic syndrome (Nieuwenhuizen & Rutters, 2008; Rosmond, 2005). Other studies provide evidence for chronic pain-related reductions in baroreflex sensitivity indicating altered autonomic function (Chung et al, 2008; Furlan et al, 2005; Reyes Del Paso, Garrido, Pulgar, Martín-Vázquez, Duschek, 2010; Spaziani, 2008), absence of natural analgesia typically associated with BP elevations (Bruehl, Chung, Diedrich, Diedrich, Robertson, 2008; Olsen et al, in press; Bruehl, Chung, & Chont, 2010; Bruehl, Chung, Ward, Johnson, & McCubbin, 2002), and possible alterations in neurotransmitter function including opioid (Bruehl & Chung, 2004; Bruehl, McCubbin, & Harden, 1999; Spaziani et al, 2008) and alpha-2 adrenergic (Chung et al, 2008) systems. These findings suggest that chronic pain is associated with changes in both the central and peripheral nervous systems that could provide alternative pathways for elevated CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…The BP variables used in the analyses below reflected the mean of these four resting BP readings. Because previous studies have often shown little association between diastolic BP (DBP) and evoked pain measures [1,2,10,11,19,25], the results below focus on the influences of systolic BP (SBP). As expected, analyses for DBP paralleling those described below for SBP revealed no significant main or interaction effects involving DBP (all p > .23; results not detailed).…”
Section: Methodsmentioning
confidence: 99%
“…These BP increases trigger baroreceptors that activate descending pain inhibitory pathways from the brain to produce analgesic effects and restore cardiovascular homeostasis [9]. Although mechanisms underlying this BP-related hypoalgesia in humans are not fully understood, there is evidence that both endogenous opioid and α 2 -adrenergic pathways may be involved [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of C-reactive protein and obesity are associated with higher levels of pain in patients with OA but the impact on postoperative pain is not known [22]. Lower resting blood pressure levels are been associated with lower acute pain thresholds [23]. …”
Section: Methodsmentioning
confidence: 99%